Complete nucleotide sequence of a Citrobacter freundii plasmid carrying KPC-2 in a unique genetic environment - Yao, Yancheng; Imirzalioglu, Can; Hain, Torsten; Kaase, Martin; Gatermann, Soeren; Exner, Martin; Mielke, Martin; Hauri, Anja; Dragneva, Yolanta; Bill, Rita; Wendt, Constanze; Wirtz, Angela; et al. (My University, 2014)
The complete and annotated nucleotide sequence of a 54,036-bp plasmid harboring a blaKPC-2 gene that is clonally present in Citrobacter isolates from different species is presented. The plasmid belongs to incompatibility group N (IncN) and harbors the class A carbapenemase KPC-2 in a unique genetic environment.
Keywords: ddc:610